Mycobacterium intracellulare infection in a capybara (Hydrochoerus hydrochaeris) - Pezzone, Natalia (2013)
This report describes the first case of Mycobacterium intracellulare infection with typical granulomatous lesions of mycobacteriosis in a capybara (Hydrochoerus hydrochaeris). The individual was a captive-bred young female, part of the control group of an experimental study on stress. Multiple granulomatous lesions were detected in a mesenteric lymph node of this young female. Mycobacterial infection was confirmed by bacteriologic culture and molecular identification methods. Clinical lesions were characterized by histopathology.